Optimizing a meshless method for the simulation of the extrusion of non-Newtonian materials. (15th October 2021) - Costa, R.O.S.S.; Belinha, J.; Natal Jorge, R.M.; Rodrigues, D.E.S.
Graphical abstract: Image, graphical abstract Abstract: In this work, the Radial Point Interpolation Method (RPIM), a meshless method, is used to simulate the extrusion of non-Newtonian materials. This is a key phase in the Fused Filament Fabrication (FFF), a 3D printing process based on the extrusion of semi-molten thermoplastic filaments. Using the flow formulation (following a Lagrangian approach) and considering the materials as non-Newtonian fluids, the velocity and pressure fields are computed. The developed numerical tool takes advantage of the easy remeshing procedure associated with meshless methods. The performance of the algorithm is optimized through several parametric studies by varying the nodal meshes, integration meshes, solution methods, and the number of nodes within the influence-domains of the meshless formulation. Thus, this work addresses the accuracy and stability of the present numerical approach and provides guidelines and optimal parameters to accurately simulate the process. Due to the similarity of its behaviour, the numerical examples obtained from the literature for the extrusion of aluminium (following a power-law constitutive relationship) are used to validate this new approach. In the end, this work applies, for the first time in the literature, an advanced discretization technique to the modelling and numerical simulation of the extrusion process, enhancing the state-of-the-art concerning meshless methods and the simulation of the extrusion process for the future improvement of forming processes and/or extrusion-based additive manufacturing processes like the FFF.